PENYELESAIAN SENGKETA MENGENAI ADANYA SERTIFIKAT GANDA TERHADAP HAK MILIK ATAS TANAH SERTIFIKAT (DI DESA TANJUNG JAYA) - Caesarrio, Adzan Dylan (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Land is a basic need for every human being. therefore, land is often the object of disputes. Land disputes that occur on the basis of certificate forgery are rife in Indonesia. This happens because the price of land is expensive and there are still many landowners who have not registered their land and the local community the government and the National Land Agency are less careful in issuing certificates because there is no certified land data. So, when fraud occurs in the issuance of land certificates, no one knows from the beginning, but when the land is about to be sold, then a land dispute arises. As for the formulation of the problem in writing this skrispi is How is the legal regulation of the position of the certificate in the mastery of land rights? How is the settlement of land disputes regarding the existence of multiple certificates on land ownership rights in Tanjung Jaya village? And tunjuan in this study To find out the legal arrangements about the position of the certificate in the mastery of land rights, To find out how to resolve disputes over double certificates on land rights in Tanjung Jaya village. The method used in this research is normative juridical legal research. The data used are sourced from primary and secondary legal sources, interviews, and literature studies. The thinking process is used inductively in this research. The results of this study concluded that Mr. Maman paid for the land from Mr. Maman. pak santa as the owner of the old certificate with a sum of money 100,000,000. there are several processes being carried out to resolve land disputes regarding multiple certificates. In addition, the way to resolve land disputes regarding the existence of duplicate certificates can only be done through court channels or through out-of-court channels. Hopefully, land disputes related to duplicate certificates will no longer occur in Indonesia.